A case of severe babesiosis treated successfully with exchange transfusion. (September 2015) - Tanyel, Esra; Guler, Nil; Hokelek, Murat; Ulger, Fatma; Sunbul, Mustafa
Summary: Babesiosis is a zoonotic disease that may be asymptomatic or result in severe clinical conditions, with severe hemolysis, hepatic, and renal failure, in humans. Clinical symptoms depend on the species and immune status of the host. The disease is especially severe in those of advanced age, those with an immune deficiency, and the splenectomized. A severe case of babesiosis that developed in a splenectomy patient is presented here; the patient was admitted from a rural region with severe anemia and a deterioration in her general condition, with an initial diagnosis of malaria. In such situations, an exchange transfusion (ET), in addition to antimicrobial treatment, could be lifesaving.